Gel polymer electrolyte composition attaining shortened crosslinking time, secondary battery including the same, and manufacturing method of the secondary battery
By using a gel polymer electrolyte composition containing a specific quinone oligomer and a cyclic amine catalyst in the secondary battery, the problem of long cross-connection time in the prior art is solved, and the manufacturing efficiency and cost reduction are achieved.
Patent Information
- Application Number
- JP2025008523
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-03-31
- Filing Date
- 2025-01-21
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2043-01-11
AI Technical Summary
In the prior art, the cross-connection time of gel polymer electrolyte in secondary batteries is long, resulting in low manufacturing efficiency and increased cost.
The cross-linking time is shortened by heat treatment by using a gel polymer electrolyte composition comprising a specific quinone oligomer, a single or multicyclic cyclic amine catalyst, a polymer starter, anhydrous solvent and a lithium salt.
The cross-connection time of gel polymer electrolyte is significantly shortened, manufacturing efficiency is improved, and unit cost is reduced.
Smart Images

Figure 2025063252000001_ABST
Abstract
Description
[Technical field]
[0001] This application claims the benefit of priority based on Korean Patent Application No. 10-2022-0040568 dated March 31, 2022, and all contents disclosed in the documents of that Korean patent application are incorporated herein by reference.
[0002] The present invention relates to a gel polymer electrolyte composition having a shortened crosslinking time, a secondary battery containing the same, and a method for producing the secondary battery. [Background technology]
[0003] In recent years, rechargeable secondary batteries have been widely used as energy sources for wireless mobile devices. Secondary batteries are also attracting attention as energy sources for electric vehicles and hybrid electric vehicles, which have been proposed as a solution to address air pollution caused by existing gasoline and diesel vehicles that use fossil fuels. Therefore, the types of applications that use secondary batteries are becoming increasingly diverse due to the advantages of secondary batteries, and secondary batteries are expected to be applied to many more fields and products in the future.
[0004] A secondary battery has a structure in which an electrode assembly is housed in a battery case together with an electrolyte, and the electrode assembly is sufficiently impregnated and wetted with the electrolyte to exhibit electrical performance. However, electrolyte leakage can occur during charging and discharging, which can cause battery cell failure and even fire.
[0005] Gel polymer electrolytes have been researched as a method to prevent electrolyte leakage. However, gel polymer electrolytes require a cross-linking process after the electrolyte is injected into the battery. Therefore, the cross-linking process takes a long time, which reduces the efficiency of the process and increases the manufacturing cost.
[0006] Therefore, there is a need for a technology that can reduce the curing time due to the cross-linking reaction within the electrolyte while still introducing a gel polymer electrolyte to prevent electrolyte leakage. Summary of the Invention [Problem to be solved by the invention]
[0007] The present invention has been invented to solve the above problems, and an object of the present invention is to provide a gel polymer electrolyte composition that can significantly reduce the curing time compared to existing compositions, and a secondary battery including the same. [Means for solving the problem]
[0008] The present invention provides a composition for a gel polymer electrolyte. In one embodiment, the composition for a gel polymer electrolyte according to the present invention includes an oligomer represented by the following chemical formula 1, a hardening accelerator which is a monocyclic or polycyclic cyclic amine compound, a polymerization initiator, a non-aqueous solvent, and a lithium salt.
[0009] [ka]
[0010] In the above chemical formula 1, R is hydrogen or alkylene having 1 to 5 carbon atoms substituted with an alkyl group having 1 to 5 carbon atoms, and m is an integer of 1 to 50.
[0011] In one embodiment, the gel polymer electrolyte composition has a curing time in the range of 10 minutes to 50 minutes under heat treatment conditions of 55 to 80°C.
[0012] In a specific embodiment, the content of the oligomer is in the range of 0.1 to 30 parts by weight relative to 100 parts by weight of the total composition for gel polymer electrolyte.
[0013] In another embodiment, the cure accelerator comprises one or more of a pyrimidine type, an imidazole type, a purine type, a thiadiazole type, and a pyrrole type.
[0014] In a specific embodiment, the pyrimidine-based curing accelerator is one or more of the following chemical formulas 1-a to 1-g.
[0015] [ka]
[0016] [ka]
[0017] [ka]
[0018] [ka]
[0019] [ka]
[0020] [ka]
[0021] [ka]
[0022] In a specific embodiment, the imidazole-based curing accelerator is one or more of the following chemical formulas 2-a to 2-i.
[0023] [ka]
[0024] [ka]
[0025] [ka]
[0026] [ka]
[0027] [ka]
[0028] [ka]
[0029] [ka]
[0030] [ka]
[0031] [ka]
[0032] In a specific embodiment, the purine-based hardening accelerator is represented by the following chemical formula 3-a.
[0033] [ka]
[0034] In a specific embodiment, the thiadiazole system is one or more of the following formulas 4-a to 4-b:
[0035] [ka]
[0036] [ka]
[0037] In a specific embodiment, the pyrrole-based curing accelerator is one or more of the following chemical formulas 5-a to 5-c.
[0038] [ka]
[0039] [ka]
[0040] [ka]
[0041] In one embodiment, the content of the hardening accelerator is in the range of 0.01 to 10 parts by weight with respect to 100 parts by weight of the entire composition for gel polymer electrolyte.
[0042] The present invention also provides a method for manufacturing a lithium secondary battery by applying the above-mentioned gel polymer electrolyte composition. In one embodiment, the method for manufacturing a lithium secondary battery according to the present invention includes the step of injecting the above-mentioned gel polymer electrolyte composition into a battery case in a state where an electrode assembly including a positive electrode, a negative electrode, and a separator disposed between the positive electrode and the negative electrode is housed in a battery case.
[0043] In one embodiment, the method for producing a lithium secondary battery further includes a step of performing thermal crosslinking for a period ranging from 10 minutes to 50 minutes after the step of injecting the gel polymer electrolyte composition into the battery case.
[0044] In a specific embodiment, the step of thermal crosslinking is carried out at a temperature in the range of 55 to 80°C.
[0045] In another specific embodiment, the manufacturing method according to the present invention further includes a wetting step of waiting for 1 minute to 30 hours between the step of injecting the gel polymer electrolyte composition into the battery case and the step of performing thermal crosslinking.
[0046] In another specific embodiment, the method of the present invention further comprises, after the thermal crosslinking step, one or more of an activation step and a degassing step.
[0047] The present invention also provides a secondary battery manufactured by the above-mentioned method. In one embodiment, the lithium secondary battery according to the present invention includes an electrode assembly including a positive electrode, a negative electrode, and a separator disposed between the positive electrode and the negative electrode, a battery case that houses and seals the electrode assembly, and a gel polymer electrolyte composition injected into the battery case housing the electrode assembly. The gel polymer electrolyte composition is as described above.
[0048] In a specific embodiment, the lithium secondary battery is a pouch-type battery. Effect of the Invention
[0049] The present invention makes it possible to increase the efficiency of the manufacturing process for a secondary battery using a thermally crosslinked gel polymer electrolyte and to improve the quality of the manufactured product. [Brief description of the drawings]
[0050] [Figure 1] 1 is a schematic diagram illustrating a leakage evaluation process for a pouch-type secondary battery according to an embodiment of the present invention; DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0051] The present invention will be described in detail below. Before that, the terms and words used in the specification and claims should not be interpreted to be limited to their general or dictionary meanings, but should be interpreted as meanings and concepts that match the technical idea of the present invention based on the principle that the inventor can appropriately define the concept of the term to best describe his own invention.
[0052] The present invention provides a composition for a gel polymer electrolyte. In one embodiment, the composition for a gel polymer electrolyte according to the present invention includes an oligomer, a curing accelerator which is a monocyclic or polycyclic cyclic amine compound, a polymerization initiator, a non-aqueous solvent, and a lithium salt.
[0053] In the present invention, "monocyclic" includes the case where one cyclic structure is contained in the structural formula. "Polycyclic" means the case where two or more, specifically 2 to 4, cyclic structures are contained in the structural formula, and the case where two or more cyclic structures are fused or compounded with each other is also included.
[0054] The present invention significantly increases the gelation rate of the electrolyte by adding a curing accelerator that accelerates the crosslinking reaction of the oligomer.
[0055] As an example, the oligomer may be a PPC (Polypropylene carbonate) series oligomer. In one embodiment, the oligomer is represented by the following Chemical Formula 1:
[0056] [ka]
[0057] In the above chemical formula 1, R is hydrogen or alkylene having 1 to 5 carbon atoms substituted with an alkyl group having 1 to 5 carbon atoms, and m is an integer of 1 to 50.
[0058] Specifically, the R is an arylene having 1 to 3 carbon atoms, more specifically, an arylene having 2 carbon atoms substituted with a methyl group. The m is an integer of 1 to 10, an integer of 2 to 5, an integer of 2 to 3, or 2.
[0059] In one embodiment, the content of the oligomer in the present invention is in the range of 0.1 to 30 parts by weight relative to 100 parts by weight of the total composition for gel polymer electrolyte. More specifically, the content of the oligomer is in the range of 1 to 10 parts by weight, 2 to 8 parts by weight, or 3 to 5 parts by weight. The content of the oligomer is in a range that prevents leakage of the electrolyte when applied to a secondary battery, while not deteriorating the performance of the secondary battery.
[0060] The curing temperature of the composition for gel polymer electrolyte may vary depending on the type of polymerization initiator. In one embodiment, the composition for gel polymer electrolyte undergoes a crosslinking reaction under heat treatment conditions of 55 to 80°C, 60 to 75°C, or 62 to 68°C, and in this case, the curing time is in the range of 10 to 50 minutes, 10 to 40 minutes, or 20 to 40 minutes. The composition for gel polymer electrolyte reduces the curing time by 25% or more compared to the conventional method by using a curing accelerator.
[0061] In one embodiment, the curing accelerator includes one or more of pyrimidines, imidazoles, purines, thiadiazoles, and pyrroles. The present invention includes the use of one or more of such curing accelerators in combination.
[0062] In a specific embodiment, the pyrimidine-based curing accelerator is one or more of the following chemical formulas 1-a to 1-g.
[0063] [ka]
[0064] [ka]
[0065] [ka]
[0066] [ka]
[0067] [ka]
[0068] [ka]
[0069] [ka]
[0070] In a specific embodiment, the imidazole-based curing accelerator is one or more of the following chemical formulas 2-a to 2-i.
[0071] [ka]
[0072] [ka]
[0073] [ka]
[0074] [ka]
[0075] [ka]
[0076] [ka]
[0077] [ka]
[0078] [ka]
[0079] [ka]
[0080] In a specific embodiment, the purine-based hardening accelerator is represented by the following formula 3-a:
[0081] [ka]
[0082] In a specific embodiment, the thiadiazole-based curing accelerator is one or more of the following chemical formulas 4-a to 4-b.
[0083] [ka]
[0084] [ka]
[0085] In a specific embodiment, the pyrrole-based curing accelerator is one or more of the following chemical formulas 5-a to 5-c.
[0086] [ka]
[0087] [ka]
[0088] [ka]
[0089] In the present invention, the content of the curing accelerator is in the range of 0.01 to 10 parts by weight relative to 100 parts by weight of the total composition for gel polymer electrolyte. Specifically, the content of the curing accelerator is in the range of 0.1 to 10 parts by weight, 0.01 to 5 parts by weight, 0.2 to 5 parts by weight, or 0.5 to 2 parts by weight. The content of the curing accelerator is in the range that can sufficiently reduce the curing speed while minimizing the input amount.
[0090] The present invention also provides a method for manufacturing a lithium secondary battery using the above-mentioned gel polymer electrolyte. In one embodiment, the method for manufacturing a lithium secondary battery according to the present invention includes injecting a gel polymer electrolyte composition into a battery case while housing an electrode assembly including a positive electrode, a negative electrode, and a separator disposed between the positive electrode and the negative electrode in a battery case.
[0091] In the present invention, the above-mentioned gel polymer electrolyte composition is injected into a battery case containing an electrode assembly to manufacture a secondary battery. Then, a process of gelling the gel polymer electrolyte composition by heat treatment is performed. Specifically, the present invention includes a step of performing thermal crosslinking for 10 to 50 minutes after the step of injecting the gel polymer electrolyte composition into the battery case. The step of performing thermal crosslinking is a process of inducing a crosslinking reaction of the injected gel polymer electrolyte to harden it. The hardening time is in the range of 10 to 50 minutes, 10 to 40 minutes, or 20 to 40 minutes. The present invention has the effect of reducing the hardening time by 25% or more compared to the conventional method.
[0092] In addition, the temperature of the heat treatment in the step of performing thermal crosslinking may vary depending on the type of polymerization initiator added. In the present invention, for example, the curing accelerator represented by the following Chemical Formula 2 may be used. In this case, the step of performing thermal crosslinking may be performed in a temperature range of 55 to 80°C, 60 to 75°C, or 62 to 68°C.
[0093] In another embodiment, the present invention includes a wetting step of waiting for 1 minute to 30 hours between the step of injecting the gel polymer electrolyte composition into the battery case and the step of performing thermal crosslinking.
[0094] In another embodiment, the present invention includes one or more of an activation step and a degassing step after the thermal crosslinking step.
[0095] The present invention also provides a secondary battery manufactured by the above-mentioned manufacturing method. In one embodiment, the secondary battery according to the present invention includes an electrode assembly including a positive electrode, one negative electrode, and a separator disposed between the positive electrode and the negative electrode, a battery case that houses and seals the electrode assembly, and a gel polymer electrolyte composition injected into the battery case housing the electrode assembly. The gel polymer electrolyte composition is as described above.
[0096] Depending on the method of stacking the electrode assemblies, they can be classified into a wound jelly roll type and a stack type in which the electrodes are stacked sequentially. Also, depending on the shape of the battery case, secondary batteries can be classified into cylindrical batteries and prismatic batteries in which the electrode assembly is housed in a cylindrical or prismatic metal can, and pouch batteries in which the electrode assembly is housed in a pouch case of an aluminum laminate sheet. The secondary battery of the present invention can be a cylindrical, prismatic, or pouch type secondary battery, and preferably a pouch type secondary battery.
[0097] Meanwhile, the case may be a laminate sheet including a metal layer and a resin layer. Specifically, the laminate sheet may be an aluminum laminate sheet. The battery case of the laminate sheet may include a lower case having a recessed receiving portion and an outer shell extending from the receiving portion, and an upper case joined to the lower case by thermal fusion.
[0098] The components of the secondary battery of the present invention will be described below.
[0099] A positive electrode, which is one of the components of a secondary battery, has a structure in which a positive electrode active material layer is laminated on one or both sides of a positive electrode current collector. In one example, the positive electrode active material layer includes a positive electrode active material, a conductive material, a binder polymer, etc., and may further include a positive electrode additive commonly used in the art as necessary.
[0100] The positive electrode active materials may be the same or different lithium-containing oxides. As the lithium-containing oxide, a lithium-containing transition metal oxide may be used.
[0101] For example, lithium-containing transition metal oxides include Li x CoO2(0.5 <x<1.3)、Li x NiO2(0.5 <x<1.3)、Li x MnO2(0.5 <x<1.3)、Li x Mn2O4(0.5 <x<1.3)、Li x (Ni a Co b Mn c )O2(0.5 <x<1.3、0<a<1、0<b<1、0<c<1、a+b+c=1)、Li x Ni 1-y Co y O2(0.5 <x<1.3、0<y<1)、Li x Co 1-y Mn y O2(0.5 <x<1.3、0≦y<1)、Li x Ni 1-y Mn y O2(0.5 <x<1.3、0≦y<1)、Lix (Ni a Co b Mn c )O4 (0.5 < x < 1.3, 0 < a < 2, 0 < b < 2, 0 < c < 2, a + b + c = 2), Li x Mn 2-z Ni z O4 (0.5 < x < 1.3, 0 < z < 2), Li x Mn 2-z Co z O4 (0.5 < x < 1.3, 0 < z < 2), Li x CoPO4 (0.5 < x < 1.3), and Li x FePO4 (0.5 < x < 1.3), and can be any one selected from the group consisting of mixtures of two or more thereof. Further, the lithium-containing transition metal oxide can also be coated with a metal or metal oxide such as aluminum (Al). In addition to the lithium-containing transition metal oxide, one or more of sulfide, selenide, and halide can be used.
[0102] The above positive electrode active material can be contained in the positive electrode active material layer in the range of 94.0 to 98.5% by weight. When the content of the positive electrode active material satisfies the above range, it is advantageous in terms of manufacturing a high-capacity battery and imparting sufficient conductivity of the positive electrode and adhesion between electrode materials.
[0103] The current collector used for the above positive electrode is a metal with high conductivity, and any metal can be used as long as it can easily adhere to the positive electrode active material slurry and is non-reactive within the voltage range of the electrochemical element. Specifically, non-limiting examples of the current collector for the positive electrode include foils made of aluminum, nickel, or combinations thereof. The positive electrode active material layer further contains a conductive material.
[0104] The conductive material is often a carbon-based conductive material, and includes a sphere-type or needle-type carbon-based conductive material. The spherical carbon-based conductive material fills pores, which are vacant spaces between active material particles, when mixed with a binder, thereby improving physical contact between the active materials, reducing interfacial resistance, and improving adhesion between the lower positive electrode active material and the current collector.
[0105] The conductive material may be contained in the positive electrode active material layer in an amount of 0.5 to 5% by weight. When the content of the conductive material satisfies the above range, sufficient conductivity of the positive electrode is imparted, and there is an effect of reducing the interfacial resistance between the electrode current collector and the active material.
[0106] The binder polymer may be any binder commonly used in the art without limitation. For example, the binder may be a water-insoluble polymer that is soluble in an organic solvent and insoluble in water, or a water-soluble polymer that is insoluble in an organic solvent and soluble in water. The water-insoluble polymer may be one selected from the group including polyvinylidene fluoride (PVDF), polyvinylidene chloride (PVDC), polyacrylonitrile (PAN), polypropylene oxide (PPO), polyethylene oxide-propylene oxide copolymer (PEO-PPO), polytetrafluoroethylene (PTFE), polyimide (PI), polyetherimide (PEI), styrene butadiene rubber (SBR), polyacrylate, and derivatives thereof.
[0107] The water-soluble polymer may be one or more selected from the group including various cellulose derivatives such as carboxymethylcellulose (CMC), methylcellulose (MC), cellulose acetate phthalate (CAP), hydroxypropylmethylcellulose (HPMC), and hydroxypropylmethylcellulose phthalate (HPMCP).
[0108] The content of the binder polymer is proportional to the content of the conductive material contained in the upper and lower positive electrode active material layers, because it provides adhesive strength to the conductive material, which has a relatively small particle size compared to the active material, and because an increase in the content of the conductive material requires more binder polymer, whereas a decrease in the content of the conductive material requires less binder polymer.
[0109] The negative electrode has a structure in which a negative electrode active material layer is laminated on one or both sides of a negative electrode current collector. In one example, the negative electrode active material layer includes a negative electrode active material, a conductive material, a binder polymer, etc., and may further include a negative electrode additive commonly used in the art, as necessary.
[0110] The negative electrode active material may include a carbon material, lithium metal, silicon, or tin. When a carbon material is used as the negative electrode active material, both low crystalline carbon and high crystalline carbon may be used. Typical low crystalline carbons are soft carbon and hard carbon, and typical high crystalline carbons are natural graphite, kish graphite, pyrolytic carbon, mesophase pitch based carbon fiber, carbon microbeads, mesophase pitches, and high temperature fired carbons such as petroleum or coal tar pitch derived cokes.
[0111] Non-limiting examples of the current collector used in the negative electrode include foils made of copper, gold, nickel, copper alloys, or combinations thereof. The current collector may also be used by laminating a substrate made of the above materials.
[0112] The negative electrode may also include conductive materials and binders commonly used in the art.
[0113] The separator may be any porous substrate used in lithium secondary batteries, for example, a polyolefin-based porous membrane or nonwoven fabric, but is not limited thereto.
[0114] Examples of the polyolefin-based porous membrane include membranes formed from polyolefin-based polymers such as polyethylene (e.g., high density polyethylene, linear low density polyethylene, low density polyethylene, ultra-high molecular weight polyethylene), polypropylene, polybutylene, and polypentene, either alone or in combination.
[0115] Examples of the nonwoven fabric include, in addition to polyolefin-based nonwoven fabric, nonwoven fabrics formed from polymers such as polyethylene terephthalate, polybutylene terephthalate, polyester, polyacetal, polyamide, polycarbonate, polyimide, polyether ether ketone, polyether sulfone, polyphenylene oxide, polyphenylene sulfide, and polyethylene naphthalene, either alone or in combination. The structure of the nonwoven fabric may be a spunbonded or meltblown nonwoven fabric made of long fibers.
[0116] The thickness of the porous substrate is not particularly limited, but may be 5 to 50 μm, and the size and porosity of the pores present in the porous substrate are also not particularly limited, but may be 0.01 to 50 μm and 10 to 95%, respectively.
[0117] Meanwhile, in order to improve the mechanical strength of the separator formed of the porous substrate and to prevent a short circuit between the positive electrode and the negative electrode, a porous coating layer including inorganic particles and a binder polymer may be further included on at least one surface of the porous substrate.
[0118] The electrolyte may include an organic solvent and an electrolyte salt, and the electrolyte salt is a lithium salt. The lithium salt may be any salt commonly used in non-aqueous electrolytes for lithium secondary batteries. For example, a lithium salt having a cation such as Li + Contains F as an anion - , Cl - , Br - , I - , NO 3- , N(CN) 2- , B.F. 4- , ClO 4- , AlO 4- , AlCl 4- , P.F. 6- , SbF 6- , AsF 6- , BF2C2O 4- , B.C.4O 8- , (CF3)2PF 4- , (CF3)3PF 3- , (CF3)4PF 2- , (CF3)5PF - , (CF3)6P - , CF3SO 3- , C4F9SO 3- , CF3CF2SO 3- , (CF3SO2)2N - , (FSO2)2N - , CF3CF2(CF3)2CO - , (CF3SO2)2CH - , (SF5)3C - , (CF3SO2)3C - , CF3(CF2)7SO 3- , CF3CO 2- , CHCO 2- , SCN - , and (CF3CF2SO2)2N - It may include at least one selected from the group consisting of:
[0119] The organic solvent contained in the electrolyte may be any organic solvent generally used in secondary battery electrolytes, and may be used without limitation, for example, ethers, esters, amides, linear carbonates, cyclic carbonates, etc., each of which may be used alone or in combination of two or more. Among these, representative examples include carbonate compounds that are cyclic carbonates, linear carbonates, or mixtures thereof.
[0120] Specific examples of the cyclic carbonate compound include any one selected from the group consisting of ethylene carbonate (EC), propylene carbonate (PC), 1,2-butylene carbonate, 2,3-butylene carbonate, 1,2-pentylene carbonate, 2,3-pentylene carbonate, vinylene carbonate, vinylethylene carbonate, and halides thereof, or a mixture of two or more of these. Examples of these halides include, but are not limited to, fluoroethylene carbonate (FEC).
[0121] Specific examples of the linear carbonate compound include, but are not limited to, any one selected from the group consisting of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate, ethyl methyl carbonate (EMC), methyl propyl carbonate, and ethyl propyl carbonate, or a mixture of two or more of these.
[0122] In particular, ethylene carbonate and propylene carbonate, which are cyclic carbonates among the above carbonate-based organic solvents, are high-viscosity organic solvents with high dielectric constants, and can dissociate lithium salts in the electrolyte more effectively. When such cyclic carbonates are mixed with linear carbonates having low viscosity and low dielectric constants, such as dimethyl carbonate and diethyl carbonate, in a suitable ratio, an electrolyte having higher electrical conductivity can be produced.
[0123] In addition, the ether among the organic solvents may be any one selected from the group consisting of dimethyl ether, diethyl ether, dipropyl ether, methyl ethyl ether, methyl propyl ether, and ethyl propyl ether, or a mixture of two or more of these, but is not limited thereto.
[0124] Among the organic solvents, the ester may be any one selected from the group consisting of methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, γ-valerolactone, γ-caprolactone, σ-valerolactone, and ε-caprolactone, or a mixture of two or more of these, but is not limited thereto.
[0125] The electrode assembly may be of a lamination / stack type in which unit cells are stacked with a separator interposed therebetween, or of a stack / folding type in which unit cells are wound around a separator sheet.
[0126] The electrode assembly is manufactured by applying electrode active materials to positive and negative current collectors to form composite layers, manufacturing positive and negative electrodes with pinholes in the electrode tabs and electrode plates using a notching device, and bonding the positive and negative electrodes to a separator without pinholes. The type of the separator is not limited, but may be an organic / inorganic composite porous SRS (Safety-Reinforcing Separators) separator.
[0127] Specifically, the SRS separator is manufactured by using inorganic particles and a binder polymer as active layer components on a polyolefin-based separator substrate, and has a uniform pore structure formed by the pore structure contained in the separator substrate itself and the interstitial volume between the inorganic particles, which are active layer components. When using such an organic / inorganic composite porous separator, it has an advantage that the increase in the thickness of the battery due to swelling during the formation process can be suppressed compared to when using a general separator, and when a polymer that can be gelled when impregnated with a liquid electrolyte is used as the binder polymer component, it can be used simultaneously as an electrolyte. In addition, the organic / inorganic composite porous separator has a feature that the battery assembly process can be easily performed because it can show excellent adhesive properties by adjusting the content of the inorganic particles and binder polymer, which are active layer components in the separator.
[0128] The present invention will be described in more detail below with reference to examples. Since the present invention can be modified in various ways and has various embodiments, specific examples will be illustrated and described in detail in the text. However, this is not intended to limit the present invention to the specific disclosed form, and should be understood as including all modifications, equivalents, or alternatives within the spirit and technical scope of the present invention.
[0129] <Example 1> LiPF6 was dissolved as a lithium salt at a concentration of 1M in a solvent in which ethylene carbonate (EC) and ethyl methyl carbonate (EMC) were mixed at a volume ratio of 3:7, and additives were added according to the content relative to the total weight of the gel polymer electrolyte as shown in Table 1 below to prepare gel polymer electrolyte compositions.
[0130] Specifically, the oligomer was added in an amount of 4% by weight, and the structural formula of the oligomer was Chemical Formula 1, where R is an alkylene having 2 carbon atoms substituted with a methyl group, and m is an integer ranging from 2 to 3.
[0131] The curing accelerator was added at a content of 4 wt.%, and the structural formula of the oligomer was as shown in Chemical Formula 1-c below.
[0132] [ka]
[0133] As a polymerization initiator, a thermal initiator, FUJIFILM WAKO's azo-based initiator V-59 product, was used at a content of 1 wt %.
[0134] The positive electrode active material is LiNi with a particle size of 5 μm. 0.5 Mn 1.5 O4 was prepared and mixed with polyvinylidene fluoride as a carbon-based conductive agent and binder in N-methylpyrrolidone (NMP) in a weight ratio of 94:3:3 to form a slurry, which was then cast onto an aluminum sheet, dried in a vacuum oven at 120°C, and rolled to produce a positive electrode.
[0135] Separately, a negative electrode active material was prepared by mixing artificial graphite and silicon oxide (SiO2) in a weight ratio of 9:1. 97 parts by weight of the negative electrode active material and 3 parts by weight of styrene-butadiene rubber (SBR) were mixed with water to form a slurry, which was then cast onto a copper sheet, dried in a vacuum oven at 130°C, and rolled to produce a negative electrode.
[0136] The positive and negative electrodes obtained above were inserted into a case with a separator made of 18 μm polypropylene, and the gel polymer electrolyte composition was then poured in. After that, the case was cured at 65° C. for 30 minutes to prepare a pouch-type lithium secondary battery.
[0137] <Examples 2 to 6> Gel polymer electrolyte compositions were prepared in the same manner as in Example 1, except that the curing accelerator was added at a content of 4 wt % and the oligomer structural formulas were the following chemical formulas 2-e, 2-i, 3-a, 4-b, and 5-c, respectively.
[0138] [ka]
[0139] [ka]
[0140] [ka]
[0141] [ka]
[0142] [ka]
[0143] A lithium secondary battery was manufactured in the same manner as in Example 1 using the prepared gel polymer electrolyte composition.
[0144] <Comparative Example 1> An electrolyte composition was prepared by dissolving LiPF6 as a lithium salt at a concentration of 1M in a solvent in which ethylene carbonate (EC) and ethyl methyl carbonate (EMC) were mixed in a volume ratio of 3:7.
[0145] The positive electrode active material is LiNi with a particle size of 5 μm. 0.5 Mn 1.5 O4 was prepared and mixed with polyvinylidene fluoride as a carbon-based conductive agent and binder in N-methylpyrrolidone (NMP) in a weight ratio of 94:3:3 to form a slurry, which was then cast onto an aluminum sheet, dried in a vacuum oven at 120°C, and rolled to produce a positive electrode.
[0146] Separately, a negative electrode active material was prepared by mixing artificial graphite and silicon oxide (SiO2) in a weight ratio of 9:1. 97 parts by weight of the negative electrode active material and 3 parts by weight of styrene-butadiene rubber (SBR) were mixed with water to form a slurry, which was then cast onto a copper sheet, dried in a vacuum oven at 130°C, and rolled to produce a negative electrode.
[0147] A separator made of 18 μm polypropylene was placed between the positive electrode and the negative electrode obtained above, and the resulting positive electrode and negative electrode were inserted into a case, and the prepared electrolyte composition was then injected thereinto to prepare a pouch-type lithium secondary battery.
[0148] <Comparative Example 2> LiPF6 was dissolved as a lithium salt at a concentration of 1M in a solvent in which ethylene carbonate (EC) and ethyl methyl carbonate (EMC) were mixed at a volume ratio of 3:7, and additives were added according to the content relative to the total weight of the gel polymer electrolyte as shown in Table 1 below to prepare gel polymer electrolyte compositions.
[0149] Using the prepared gel polymer electrolyte composition, a lithium secondary battery was prepared in the same manner as in Example 1, except that the curing time was set to 30 minutes.
[0150] <Comparative Example 3> LiPF6 was dissolved as a lithium salt at a concentration of 1M in a solvent in which ethylene carbonate (EC) and ethyl methyl carbonate (EMC) were mixed at a volume ratio of 3:7, and additives were added according to the content relative to the total weight of the gel polymer electrolyte as shown in Table 1 below to prepare gel polymer electrolyte compositions.
[0151] Using the prepared gel polymer electrolyte composition, a lithium secondary battery was prepared in the same manner as in Example 1, except that the curing time was set to 100 minutes.
[0152] <Comparative Example 4> LiPF6 was dissolved as a lithium salt at a concentration of 1M in a solvent in which ethylene carbonate (EC) and ethyl methyl carbonate (EMC) were mixed at a volume ratio of 3:7, and additives were added according to the content relative to the total weight of the gel polymer electrolyte as shown in Table 1 below to prepare gel polymer electrolyte compositions.
[0153] Using the produced gel polymer electrolyte composition, a lithium secondary battery was produced in the same manner as in Example 1, except that the curing time was set to 300 minutes.
[0154] [Table 1]
[0155] <Experimental example: Evaluation of the presence or absence of leakage> The presence or absence of electrolyte leakage was evaluated for each of the secondary batteries manufactured in Examples 1 to 6 and Comparative Examples 1 to 3. Each secondary battery was a large cell of 100 Ah class.
[0156] The evaluation process is illustrated in FIG. 1. Referring to FIG. 1, each pouch-type secondary battery 100 is a large-sized battery cell of 100 Ah class. The pouch-type secondary battery 100 has a structure in which an electrode assembly is housed in a pouch-type case. Based on the pouch-type case, a sealing area 120 is formed by heat sealing on four sides surrounding an electrode assembly housing area 110, and electrode terminals 130 are led out to both sides. One side of the lower end of each pouch-type secondary battery 100 was cut open by about d (d=25 cm), and stored at an inclination angle θ (θ=5°) at room temperature for one week. Then, the amount of electrolyte leakage from each pouch-type secondary battery 100 was measured.
[0157] If the amount of electrolyte injected was reduced by 3% or more by weight compared to the initial amount, it was determined that electrolyte leakage had occurred. The evaluation results are shown in Table 2 below.
[0158] [Table 2]
[0159] With reference to Table 2, in Examples 1 to 6, no electrolyte leakage was observed even with a curing time of 30 minutes. In contrast, in Comparative Example 1, gelation of the electrolyte did not occur, and therefore leakage was observed. With reference to Comparative Examples 2 and 3, it can be seen that when the curing accelerator according to the present invention is not added, electrolyte leakage is observed with a curing time of 30 minutes or 100 minutes. With reference to Comparative Example 4, it can be seen that when the curing accelerator is not added, no leakage is observed with a curing time of 300 minutes. [Explanation of symbols]
[0160] 100: Pouch-type secondary battery 110: Electrode assembly storage area 120: Sealing area 130: Terminal
Claims
1. An oligomer represented by the following chemical formula 1: a curing accelerator which is a monocyclic or polycyclic cyclic amine compound; A polymerization initiator, a non-aqueous solvent, and Lithium salts, 【Chemistry 1】 In the above Chemical Formula 1, R is hydrogen or an alkylene having 1 to 5 carbon atoms substituted with an alkyl group having 1 to 5 carbon atoms, The composition for a gel polymer electrolyte, wherein m is an integer of 1 to 50.
2. 2. The composition for gel polymer electrolyte according to claim 1, wherein the composition for gel polymer electrolyte has a curing time in the range of 10 to 50 minutes under heat treatment conditions of 55 to 80°C.
3. 2. The gel polymer electrolyte composition according to claim 1, wherein the content of the oligomer is in the range of 0.1 to 30 parts by weight per 100 parts by weight of the total composition for the gel polymer electrolyte.
4. The gel polymer electrolyte composition according to claim 1 , wherein the hardening accelerator comprises at least one of a pyrimidine type, an imidazole type, a purine type, a thiadiazole type, and a pyrrole type.
5. The composition for gel polymer electrolyte according to claim 4, wherein the pyrimidine-based hardening accelerator is one or more of the following formulas 1-a to 1-g. 【Chemistry 2】 【Chemistry 3】 【Chemistry 4】 【Chemistry 5】 【Chemistry 6】 【Chemistry 7】 【Chemistry 8】
6. The composition for gel polymer electrolyte according to claim 4, wherein the imidazole-based hardening accelerator is one or more of the following formulas 2-a to 2-i. 【Chemistry 9】 【Chemistry 10】 【Chemistry 11】 【Chemistry 12】 【Chemistry 13】 【Chemistry 14】 【Chemistry 15】 【Chemistry 16】 【Chemistry 17】
7. The composition for gel polymer electrolyte according to claim 4, wherein the hardening accelerator is a purine-based hardening accelerator represented by the following chemical formula 3-a: 【Chemistry 18】
8. The composition for gel polymer electrolyte according to claim 4, wherein the thiadiazole-based hardening accelerator is one or more of the following chemical formulas 4-a to 4-b. 【Chemistry 19】 【Chemistry 20】
9. The composition for gel polymer electrolyte according to claim 4, wherein the pyrrole-based hardening accelerator is one or more of the following formulas 5-a to 5-c. 【Chemistry 21】 【Chemical 22】 【Chemistry 23】
10. 2. The composition for a gel polymer electrolyte according to claim 1, wherein the content of the hardening accelerator is in the range of 0.01 to 10 parts by weight per 100 parts by weight of the total composition for a gel polymer electrolyte.
11. In a state where an electrode assembly including a positive electrode, a negative electrode, and a separator disposed between the positive electrode and the negative electrode is housed in a battery case, A method for producing a lithium secondary battery, comprising the step of injecting the gel polymer electrolyte composition according to claim 1 into a battery case.
12. After the step of injecting the gel polymer electrolyte composition into the battery case, The method for manufacturing a lithium secondary battery according to claim 11, further comprising the step of performing thermal cross-linking for a period ranging from 10 minutes to 50 minutes.
13. The method of claim 12, wherein the thermal cross-linking is performed at a temperature in the range of 55 to 80°C.
14. an electrode assembly including a positive electrode, a negative electrode, and a separator disposed between the positive electrode and the negative electrode; a battery case for housing and sealing the electrode assembly; and A lithium secondary battery comprising the gel polymer electrolyte composition according to any one of claims 1 to 10, injected into a battery case housing an electrode assembly.
15. The lithium secondary battery according to claim 14, wherein the lithium secondary battery is a pouch-type battery.
Citation Information
Patent Citations
Polycarbonate-based self-gel polymer electrolyte as well as preparation method and application thereof
CN113451640A
Solid polyelectrolyte
JP1996217868A
Polymer electrolyte and lithium polymer battery using the same
JP1998003944A
Secondary battery
JP1999260413A
Polymer electrolyte for dye-sensitized solar cells and method for manufacturing dye-sensitized solar cells using the same
JP2012514847A